Early childhood caries prevalence among children with cleft lip and palate at padjadjaran university dental hospital - Silvyani, Julia Thrisna; Setiawan, Asty Samiaty; Putri, Fidya Meditia (Odonto : Dental Journal, 2022)
Background: Cleft lip and/or palate (CL/P) is a congenital abnormality that can be a risk factor for Early Childhood Caries (ECC). ECC is caries that occur in children aged 0-71 months. Poor oral hygiene often found in CL/P patients due to anatomic defects, treatment devices, and surgical scars that can facilitate the colonization of Streptococcus mutans and Lactobacilli as caries-causing bacteria. This study aims to determine the prevalence of ECC in children with CL/P aged 2-6 years at Padjadjaran Univeristy Dental Hospital from 2018 - June of 2021.Method: The study used a descriptive observational method with a cross-sectional approach. The data used is secondary data which is CL/P patients aged 2-6 years medical records at Padjadjaran University Dental Hospital from 2018 until June 2021. The sample obtained using total sampling is 102.Result: The prevalence of ECC in children with CL/P was 46.08%. Unilateral complete palatognatoschizis was the most found CL/P cases (49.02%), including patients with ECC (21.57%). Male is the most common gender in this study (62.75%) also the gender with the most ECC (28.43%). Most children aged 13-24 months (66,67%), while 25-60 months (22,55%) had the highest ECC cases. Most of the CL/P patients came from West Java (95.10%), including patients with ECC (43.14%)Conclusion: Children with CLP have a high risk of caries, regardless in this study, the prevalence was not that high. Although, there are still a hefty amount of children who experience ECC. Oral hygiene must be a concern of parents from an early age to prevent ECC.